Effects of N-3 Fish Oil on Metabolic and Histological Parameters in NASH: A Double-Blind, Randomized, Placebo-Controlled Trial - Argo, Curtis K. (J Hepatol, 2014)
This study’s aim was to assess the histological and metabolic effects of N-3 polyunsaturated fatty acids (PUFA) versus placebo while adjusting for the impact of age and weight change in NASH patients. (ClinicalTrials.gov: NCT00681408). METHODS: Forty-one subjects with non-cirrhotic NASH were enrolled, and 34 completed the study. 17 received N-3 fish oil 3000 mg/day and 17 received placebo daily for 1 year with typical counseling on caloric intake and physical activity for all subjects. RESULTS: N-3- and placebo-treated groups showed no significant difference for the primary endpoint of NAS reduction ≥ 2 points without fibrosis progression after adjustment for known covariates (N-3, 4/17 (23.5%); placebo, 3/17, (17.6%), p=0.99). Among subjects with increased or stable weight, N-3 subjects showed a larger decrease in liver fat content by MRI than placebo-treated subjects (p=0.014 for 2nd quartile, p=0.003 for 3rd quartile of weight change). N-3 treatment showed significant fat reduction on paired analysis of image-assisted fat morphometry regardless of weight loss or gain. Exercise capacity remained markedly reduced in all subjects. No independent effects on markers of hepatocyte injury or insulin sensitivity indices were observed. CONCLUSION: N-3 PUFA at 3000 mg/day for one year did not lead to improvement in the primary outcome of histological activity in NASH patients (≥ 2 point NAS reduction). N-3 led to reduced liver fat by multiple measures. Other metabolic effects were not seen, although no detrimental effects were apparent. Whether longer duration, higher dose, or different composition of N-3 therapy would lead to additional benefit is uncertain.